Pelatihan Pengelolaan Bank Sampah pada Kelompok Karang Taruna di Mekarjaya Kota Depok (Neolectura, 2023)
The purpose of this community service is to develop and enhance the capabilities of the Karang Taruna Group in establishing a waste bank, managing the waste bank within the community, and utilizing the economic aspects of waste to provide a direct economic impact on society. The service activities for the community commenced with the steps of obtaining permits and traveling to partner locations in November 2022. The full implementation of community service activities took place in February 2023 at the Mekarjaya Sub-district Office, Sukmajaya District, Depok, West Java. This community service is conducted by providing training in the creation of a waste bank for the Karang Taruna of Mekar Jaya Sub-district. In addition to the provided training, mentoring in waste bank management is also carried out, along with providing knowledge about economic activities that can be undertaken in waste management. It is expected that after the implementation of this activity, besides addressing the main issue of waste, the waste bank can also contribute to the well-being of the community through its economically oriented management.